Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1515/nuka-2015-0148
|View full text |Cite
|
Sign up to set email alerts
|

The dose of gamma radiation from building materials and soil

Abstract: Abstract. The radioactivity of some structural building materials, rows, binders, and fi nal construction products, originating from Serbia or imported from other countries, was investigated in the current study by using the standard HPGe gamma spectrometry. The absorbed dose in the air was computed by the method of buildup factors for models of the room with the walls of concrete, gas-concrete, brick and stone. Using the conversion coeffi cients obtained by interpolation of the International Commission on Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The gamma absorbed doses rate in nGyh −1 were converted to annual effective dose in µSvy −1 , as proposed by Goran et al [53].…”
Section: Annual Effective Dose Ratementioning
confidence: 99%
“…The gamma absorbed doses rate in nGyh −1 were converted to annual effective dose in µSvy −1 , as proposed by Goran et al [53].…”
Section: Annual Effective Dose Ratementioning
confidence: 99%
“…Zato je pojam nedostatka proizvoda relativna, a ne apsolutna kategorija, koja u zavisnosti od relevantnih okolnosti svakog pojedinačnog slučaja poprima različitu sadržinu, pa je sud taj koji, u svakom konkretnom slučaju, istupa u ime javnosti i procenjuje kada određeni proizvod ne pruža bezbednost koja se s pravom može od takvog proizvoda očekivati. 43 Takođe, kada procenjuje da li proizvod ima nedostatak, sud nije vezan svrhom koju je proizvođač namenio proizvodu, već upotrebom za koju se razumno moglo očekivati da će proizvod biti korišćen. 44 Takođe, Sud je pozivajući se na istu presudu zaključio da treba primetiti da su određeni proizvodi sami po sebi nebezbedni, ali da to ne znači da su nužno proizvodi s nedostatkom -npr.…”
Section: Slučaj Gee and Others V Depuy International Limitedunclassified
“…However, such effects depend on several factors, with the dose rate and the linear energy transfer (LET) of the radiation being the most important. The dose rate is the delivery of dose per unit time and the absorbed dose is typically measured in Grays, Gy, where 1 Gy = 1 J/kg [ 10 ]. The higher the dose rate, the greater the cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the radiation protection principles in the EU, controls are recommended for building materials contributing to overall dose by the value of 0.3–1 mSv/y [ 14 ] which corresponds to Iγ = 0.5–1 for bulk materials. Besides the activity concentration index, several others have been developed over the years to evaluate the radiation exposure due to building material, e.g., alpha index [ 10 ], indoor and outdoor hazard indices [ 15 ], different dose parameters [ 16 , 17 , 18 ]. Several studies have been presented concerning the natural radioactivity of building materials [ 19 , 20 , 21 , 22 , 23 , 24 ], based on which it can be concluded that conventional building materials do not pose a radiological hazard due to gamma radiation and rarely exceed the EU annual dose criterion for radiation protection.…”
Section: Introductionmentioning
confidence: 99%